2016
DOI: 10.1111/1365-2745.12602
|View full text |Cite
|
Sign up to set email alerts
|

Exotic or not, leaf trait dissimilarity modulates the effect of dominant species on mixed litter decomposition

Abstract: 1. It has long been recognized that leaf traits exert a crucial control on litter decomposition, a key process for nutrient cycling, and that invading species can greatly alter such soil processes via changes in mixed litter trait composition. Trait effects on ecosystem processes are hypothesized to operate via changes in either dominant trait values in the community (often calculated as community-weighted mean trait values; CWM) or trait functional diversity (dissimilarity between species trait values; FD). F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
78
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(91 citation statements)
references
References 71 publications
10
78
0
Order By: Relevance
“…, Finerty et al. ). Note that the unexpected positive correlation between rooibos decomposition and CWM SSD suggests a more complex link between SSD and litter decomposition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Finerty et al. ). Note that the unexpected positive correlation between rooibos decomposition and CWM SSD suggests a more complex link between SSD and litter decomposition.…”
Section: Discussionmentioning
confidence: 99%
“…First, the invasive alien plant can introduce novel trait values to the invaded community, consequently shifting the overall trait composition of the community merely through its presence (Finerty et al. ). Many invasive alien plants are highly competitive species characterized by fast growth and resource acquisition (Wright et al.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies instead support the mass‐ratio hypothesis showing that the functional traits of the dominant species drive productivity (Paquette & Messier, ; Warren, Topping, & James, ). Similarly for litter decomposition, studies have found both diversity effects (Finerty et al., ; Scherer‐Lorenzen, ) and effects of the traits of dominant species on decomposition rates (Garnier et al., ; Tardif & Shipley, ). Probably both mechanisms matter for ecosystem function (Handa et al., ; Lohbeck et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have tested Darwin's naturalisation hypothesis, but the results are mixed (Diez, Sullivan, Hulme, Edwards, & Duncan, ; Duncan & Williams, ; Feng & van Kleunen, ; Finerty et al, ; Jiang, Tan, & Pu, ; Li, Cadotte, et al, ; Strauss, Webb, & Salamin, ; Yannelli, Koch, Jeschke, & Kollmann, ). Potential explanations are that the studies differ in the spatial and phylogenetic scales considered (Thuiller et al, ) and stages of invasions (Cadotte, Campbell, Li, Sodhi, & Mandrak, ; Li, Guo, et al, ), and are based on observations rather than experiments.…”
Section: Introductionmentioning
confidence: 99%